The Ethics of Legal Practitioners in Resource-Scarce Institutions ‒ PM Mashishi v Z Mdlala [2018] 17 BLLR 693 (LC); (2018) 39 ILJ 1607 (LC) - Nicola Whitear; Helen Kruuse (Obiter, 2019)
We consider what the court says in relation to hopeless cases in resource-scarce institutions, and consider how we could understand the required ethical conduct of legal practitioners in these situations better – specifically with reference to William Simon’s “ethical discretion” approach to lawyering. Simon’s critique of contemporary legal ethics in the United States appears to be particularly apt in the circumstances of the Mashishi case – specifically on the perceived amorality of the lawyer’s adversarial role, which results in an uninhibited pursuit of client ends, so long as they are arguably within the law.